Chlamydia trachomatis enhances HPV persistence through immune modulation - Yingying Lu; Qi Wu; Li Wang; Lingting Ji (BMC Infectious Diseases, 2024)
Abstract Chlamydia trachomatis (CT) is the most common sexually transmitted infections globally, and CT infection can enhance HPV persistence. Epidemiological analysis has shown that patients with CT/HPV coinfection have a higher risk of developing cervical cancer and exhibit more rapid progression to cervical cancer than patients with HPV infection alone. However, the mechanism has not been fully elucidated. Here, we report that CT infection supports HPV persistence by further suppressing the functions of Langerhans cells (LCs); in particular, CT further activates the PI3K pathway and inhibits the MAPK pathways in LCs, and these pathways are frequently involved in the regulation of immune responses. CT/HPV coinfection also impairs LC functions by reducing the antigen-presenting ability and density of LCs. Moreover, CT/HPV coinfection can alter T-cell subsets, resulting in fewer CD4 + and CD8 + T cells and more infiltrating Tregs. Moreover, CT/HPV coinfection decreases the CD4 + /CD8 + T cell ratio to below 1, coinfection also induces greater T lymphocytes’ apoptosis than HPV infection, thus impairing cell-mediated immunity and accelerating the progress to cervical cancer.